Topology optimization for crashworthiness and structural design of a battery electric vehicle. Issue 6 (2nd November 2021) - Zhang, Junyuan; Ning, Linan; Hao, Yumin; Sang, Tao
Abstract: Electric vehicles have become the main trend of the future development of the automotive industry due to their advantages such as energy conservation and environmental protection, strong acceleration capability, and low noise. This paper uses a volume-produced fuel passenger vehicle P5 as a prototype. Based on the given driving mode and traction battery pack layout of a battery electric vehicle (BEV) EP5, considering the static stiffness and crashworthiness simultaneously, the equivalent static load (ESL) method is used to perform multi-load topology optimization on the body-in-white (BIW) of the BEV. Then the load paths of EP5 are proposed. The front-end structures of the vehicle body are redesigned by using topology optimization and size optimization, which improve crashworthiness and fully tap the lightweight potential of EP5.